Review of utilizing the speech identification system for spoken queries in the Qur'an - Taufik Ridwan; Nuur Wachid Abdul Majid (Universitas Sarjanawiyata Tamansiswa, 2018)
The speech recognition system will produce a transcription text from the sound being tested — some speech recognition systems at the Al-Qur'an show quite good accuracy. There is a big possibility to use the speech recognition system to be an input to other systems. The use of sound as input to the system to do searches in data in a text representation is called spoken query. This paper tries to conduct a discussion on the use of speech recognition systems to become spoken queries in the Qur'an data. As a result, the speech recognition system can be used as input to the Qur'anic verse retrieval system and the tajwid checking system.